A Case of 22q11 Deletion Syndrome (22q11DS) with a Panayiotopoulos Epileptic Pattern: Are Additional Copy-Number Variations a Possible Second Hit in Modulating the 22q11DS Phenotype? - Bertini, Veronica; Valetto, Angelo; Azzarà, Alessia; Legitimo, Annalisa; Saggese, Giuseppe; Consolini, Rita; Orsini, Alessandro; Bonuccelli, Alice (Frontiers in Pediatrics, 2017)
ABSTRACT '22q11 deletion syndrome' (22q11DS) is a rare genetic syndrome, in which most patients share the same deletion, but their clinical features may vary a great deal. The genetic mechanisms underlying the variable expressivity and reduced penetrance of 22q11DS still have to be fully elucidated. Epilepsy has been reported in about 15.2% of the patients, however, few studies have focused on this topic and in most cases a detailed epileptic profile is missing. Since only a minority of patients experience epileptic seizures, 22q11deletion can be considered a predisposing factor, which is not sufficient ‘per se’ to cause epilepsy; to date, no candidate gene for epilepsy has been identified in the deleted region. We report on a 6-year-old girl with 22q11DS presenting a form of epilepsy that can be classified as ‘Panayiotopoulos syndrome’. Array CGH revealed an additional microduplication of 172 kb in 2q37, harboring three genes. One of these, DGKD (diacylglycerol kinase delta), is interrupted by the distal breakpoint of the duplication. DGKD encodes a cytoplasmic enzyme that phosphorylates diacylglycerol to produce phosphatidic acid. This is an important second messenger in a pathway of lipid signaling that has been implicated in epilepsy and other neurological diseases. Disruption of DGKD by a t(X;2) has been previously reported in a patient with epilepsy. The 2q37 microduplication was inherited from her mother, who never experienced epileptic seizures, thus this imbalance is not 'per se' sufficient to cause epilepsy. It can be hypothesized that the epileptic phenotype is provoked by the simultaneous presence of 22q11.2 deletion and 2q37 duplication. It has been shown that rare additional copy number variations outside the 22q11.2 region may modulate the risk of congenital heart defects. It is possible that also for the epileptic phenotype, the additional CNVs may represent an important modifying factor underlying the variable expressivity and incomplete penetrance in the 22q11DS.